Ionospheric Response to the Coronal Hole Activity of August 2020: A Global Multi‐Instrumental Overview - Waqar Younas; Majid Khan; C. Amory‐Mazaudier; P. O. Amaechi (Space Weather)
Abstract We have studied the ionospheric response to a coronal hole event of August 2020 using the data from global ionospheric maps, ground magnetometers and parameters from the instruments onboard SWARM and thermosphere, ionosphere, mesosphere energetics and dynamics satellites. The role of different physical drivers, responsible for observed ionospheric disturbance, has been identified. On the storm day (2 August), a steady southward directed interplanetary magnetic field Bz caused the penetration of magnetospheric convection electric field and positive storm effect in daytime sectors. As a result of prompt penetration electric field (PPEF) on 2 August, a polar‐ward expansion of day‐side ionospheric plasma. On 3 August, the signatures of both disturbance dynamo electric field (DDEF) caused by disturbed thermospheric winds and PPEF have been observed. The westward PPEF and eastward disturbance DDEF on the night‐side caused a strong enhancement in ionospheric plasma parameters at the corresponding sectors. The effect of disturbed thermospheric winds and resultant electric field persisted till the end of 7 August. The large decrease in O/N2 ratio at northern mid‐latitudes which is a consequence of the seasonal impact resulted in the negative storm effects at corresponding latitudinal regions. This study has shown that although the storm of August 2020 was a minor one, the associated high speed solar wind streams emanating from a coronal hole resulted in drastic changes in ionospheric parameters including global electron content, in situ electron density and total electron content at the equatorial ionization anomaly and equatorial electric field.